2020
DOI: 10.1002/agg2.20079
|View full text |Cite
|
Sign up to set email alerts
|

Temporal biological nitrogen fixation pattern in soybean inoculated with Bradyrhizobium

Abstract: Biological nitrogen fixation (BNF) in soybean [Glycine max (L.) Merr.] plays an important role in sustainable agriculture, reducing the limitations associated with other sources of N such as fertilizers and soils. Our major objective was to evaluate the weekly pattern of BNF in soybean influenced by nodule formation, using three different laboratory‐cultured Bradyrhizobium strains. Plants were grown in 1‐m polyvinyl chloride (PVC) columns for 17 week in a greenhouse and BNF was determined using an integrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Nitrogen fixation in soybean can vary depending on the growth stages of the plant. In general, SNF is lowest during the vegetative stage, then rapidly increases between R1 and R3 growth stages, before peaking then dropping upon pod formation (post R5 stage) (Zapata et al, 1987;Pitumpe Arachchige et al, 2020). In soybean, a significant portion (59%) of seed N is derived from remobilization of vegetative N, which represents N accumulated from SNF and soil uptake at the R5.5 stage (Ortez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen fixation in soybean can vary depending on the growth stages of the plant. In general, SNF is lowest during the vegetative stage, then rapidly increases between R1 and R3 growth stages, before peaking then dropping upon pod formation (post R5 stage) (Zapata et al, 1987;Pitumpe Arachchige et al, 2020). In soybean, a significant portion (59%) of seed N is derived from remobilization of vegetative N, which represents N accumulated from SNF and soil uptake at the R5.5 stage (Ortez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse studies conducted to evaluate the efficiency of BNF have focused on characteristics related to N assimilation capacity by the plant and to nodulation components (Arachchige et al., 2020; Grunvald et al., 2018; Hwang et al., 2014). Thus, to perform the partial diallel study, the traits N and chlorophyll contents, number of nodules, DWS, and dry weight of nodules, as well as the Z‐index, were considered.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest the impact of variation in the total count and individual nodule area on the total nodule area among these genotypes. It has been shown that nodule count and biological nitrogen fixation can have a strong relationship (Pitumpe Arachchige et al, 2020), suggesting that the ability to screen genotypes for nodule count can have a relational impact on nitrogen fixation. The size of nodules is also directly related to biological nitrogen fixation, as shown in Brun (Lawn & Brun, 1974).…”
Section: Discussionmentioning
confidence: 99%